Optimasi Parameter Mesin, Kualitas dan Kapasitas Produksi Alat Potong Ayam di Rumah Pemotongan Ayam - Baju Bawono; Tonny Yuniarto; Paulus Wisnu Anggoro (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Sleman Regency is an area that accommodates several small chicken industries. This research uses four partners, namely Chicken Slaughterhouse Small Medium Enterprises (SMEs) Arisa, Lasno, Ipin, Prayogo) which have significant obstacles in increasing the production capacity of good, neat, clean, and hygiene chicken meat and meeting halal standards. The cutting process is still manual and conventional, with quality and production capacity still minor and major fatigue impacts cutting operators. The purpose of Community Service (Abdimas) is the design of modified poultry slaughter machines that suit the needs of these partners and is associated with the selection of portable poultry machine design and manufacturing technology that can later improve the quality and capacity of proper chicken meat slaughter . The final result of this abdimas activity is in the form of (1) one unit of portable poultry machine tested to 4 partners (2) there was an increase in production capacity by 400%, up to 443% in terms of cutting capacity/day with fine cutting quality, precision (3) reduced fatigue experienced by chicken slaughter operators after the tool was completed within 7 hours / day and optimal production capacity increased 4 times, and the slaughter time of chickens is reduced by 75%.